The current state and the mechanism of the transformation of the EsG agenda by Russian companies. Part 1 - M. A. Izmailova (Модернизация, инновация, развитие, 2023)
Purpose: is to develop the mechanism of the ESG transformation of Russian companies based on a critical assessment of the evolution and modern implementation of the ESG agenda in Russia.The first part of the work presents the solution of the following research tasks: to identify the key drivers for the formation of the ESG agenda in Russia and present an assessment of its implementation by Russian companies.Methods: the study is based on the application of a set of the methods, including: theoretical analysis applied to the study and systematization of scientific publications; empirical analysis and statistical method required for quantitative and qualitative analysis of ESG characteristics; the retrospective method for determining the evolution of the ESG agenda and its trends.Results: conceptual approaches to the interpretation of the phenomena of ESG and sustainable development, which have a common generic basis with corporate social responsibility, are outlined. The growing interest of Russian business in the ESG agenda has been identified and substantiated, and the drivers for its development have been identified. The experience and motives for the implementation of the ESG agenda are analyzed, the factors influencing the level of maturity of the ESG practices of Russian companies are identified.Conclusions and Relevance: the relevance of the ESG agenda in Russia is determined by its association with the values of the country's socio-economic development, regardless of the unprecedented geo-economic confrontation and the threats to sustainable development generated by it. Drivers for the implementation of the ESG agenda are regulators and authorities, shareholders and investors, the board of directors and top management of companies; the influence of civil society is insignificant. The motives for implementing ESG requirements in business processes are related to strengthening the brand and increasing business reputation. The level of maturity of ESG practices depends on the company's industry affiliation, business size, investment needs: the best ESG practices are demonstrated by the mining and metallurgical industries, the largest business and companies with high investment needs. A deep awareness of the need for ESG transformation by stakeholders seeking to achieve social and environmental well-being, stability of economic development becomes a trigger for the sustainable development of economic systems.